1995
DOI: 10.1046/j.1475-1313.1995.9500055i.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of peripheral vision in terms of critical perception – its relevance to the visually impaired

Abstract: It is recognised that discrimination of fine detail is dependent on an intact macula with the peripheral retina being responsible for motion detection. There is evidence, however, to suggest that the peripheral retina does play a critical part in such discrimination. Studies of the performance of visually impaired school children have revealed levels of visual perception far exceeding anything that would be expected for individuals so severely handicapped. The art work of visually impaired youngsters was compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…An advantage of the integration condition over the multiple condition is less surprising in a person who is visually impaired, since the visuospatial memory system of a visually impaired person is likely to develop an exceptional capacity to cope with missing information to generate coherent representations. Although the visuospatial system of a person who is visually impaired works on the basis of limited visual experience, previous studies have suggested that it may nonetheless generate appropriate internal representations of the external visual world (see, for example, Wolffe, 1995). The cognitive processes that underlie integration tasks are centered on operational mechanisms that are overdeveloped in people who are visually impaired; thus, they determine the better performance of tasks, such as integration matrices, that mainly tap into these functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An advantage of the integration condition over the multiple condition is less surprising in a person who is visually impaired, since the visuospatial memory system of a visually impaired person is likely to develop an exceptional capacity to cope with missing information to generate coherent representations. Although the visuospatial system of a person who is visually impaired works on the basis of limited visual experience, previous studies have suggested that it may nonetheless generate appropriate internal representations of the external visual world (see, for example, Wolffe, 1995). The cognitive processes that underlie integration tasks are centered on operational mechanisms that are overdeveloped in people who are visually impaired; thus, they determine the better performance of tasks, such as integration matrices, that mainly tap into these functions.…”
Section: Discussionmentioning
confidence: 99%
“…Some cortical compensation occurs in cases of low vision. For instance, Wolffe (1995) reported that a group of youngsters were capable of painting landscapes or still lifes as accurately as sighted people, despite a severe central field loss that was due to a dense central scotoma. Thus, in the presence of a central vision loss, the peripheral retina could convey fine details that are normally detected by the macula and fovea, allowing the visual cortex to generate a clear, detailed representation of the visually presented external scenes.…”
mentioning
confidence: 99%